Educating music teachers for the 21st century - Aróstegui, José Luis (Educational futures : rethinking theory and practice, 2011)
Educating Music Teachers for the 21st Century discusses a range of teacher education programmes in music across Europe and Latin America reflecting about the shifting conditions, causes and factors in which pre-service teachers construct their musical and educational knowledge. It presents seven case studies carried out in Argentina, Brazil, Mexico, Portugal, Spain, and Sweden in order to understand the general and specific elements of new thinking in music education, and the ways these relate to the profound changes all of these countries are experiencing, within the era of cultural globalisation. In this way, this book does not only analyse specific programmes but also seeks to explore a range of issues relating to the education of music teachers that is of interest both to scholars working within music education and music teacher training, and to a wider educational audience of readers interested in such topics as changing youth cultures, globalisation, educational evaluation and teacher education